The Effect of Empowerment on The Welfare of Women Micro Business Actors Through Performance in Kutai Kartanegara District - Purwanti, Indah; Ruliana, Titin; Yudhyani, Eka (Journal La Bisecoman, 2024)
Micro, Small and Medium Enterprises (MSMEs) play a vital role in the economy, especially in developing countries like Indonesia. Although MSMEs in Kutai Kartanegara Regency are experiencing significant growth, their welfare level is still low. This study aims to explore the effect of empowerment on the welfare of women MSME players, with MSME performance as an intervening variable, to understand the factors that influence their welfare in the region. The study uses a quantitative approach, using primary data and secondary data. Primary data in this study refers to information obtained directly from respondents or from sources relevant to the research focus. Meanwhile, secondary data was obtained from various literatures, both published and unpublished, as well as from related articles or reports. This study used a non-probability sampling technique, where the sample was purposively selected with a sample size of 122 Micro Business Actors in the Kutai Kartanegara region. This study, the analytical tool used was the SmartPLS version 3.2.9 application. The data analysis process involves three stages: measurement model (outer model), structural model (inner model), and hypothesis testing through the Bootstrapping method. The results of this study show that empowerment (X) has a positive and significant influence on performance (Z), performance (Z) has a positive and significant effect on welfare (Y), empowerment (X) has a positive and significant effect on welfare (Y), empowerment (X) has a positive and significant effect on welfare (Y) through Performance (Z).